(3TQM OjhGf QDHI GHf GdYLGLs - (3CHh SYjO GdVQjQ GdLQeGfis; (3QDHI GHf GdYLGL GdHUQj,J (B145 (3g` s ((3GSeGYjd Hf Ndjd GdGfWGci s)
(3ChdgG (B:s
(3bGd QDHI Hf GdYLGL jeOM eQhGf Hf eMeO Hf eQhGf CQbfi WGQb ge GQbG hQcV ZQHGf ZOhJ s
(3BNQgG (B:s
(3hgfG eKd jbhd dGjLGQ Hfi GMOG dGSHbJg Je OjhGf QDHI Hf GdYLGL s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs